Time-reversal and rotation symmetry breaking superconductivity in Dirac materials - Chirolli, L; de Juan Sanz, F; Guinea, F (American Physical Society, 2017)
We consider mixed symmetry superconducting phases in Dirac materials in the odd-parity channel, where pseudoscalar and vector order parameters can coexist due to their similar critical temperatures when attractive interactions are of a finite range. We show that the coupling of these order parameters to unordered magnetic dopants favors the condensation of time-reversal symmetry breaking (TRSB) phases, characterized by a condensate magnetization, rotation symmetry breaking, and simultaneous ordering of the dopant moments. We find a rich phase diagram of mixed TRSB phases characterized by peculiar bulk quasiparticles, with Weyl nodes and nodal lines, and distinctive surface states. These findings are consistent with recent experiments on NbxBi2Se3 that report evidence of point nodes, nematicity, and TRSB superconductivity induced by Nb magnetic moments.